(untitled) (Baltic Journal of Sport and Health Sciences, 2017)
Background. This study aimed to examine serotonin, dopamine and cardiovascular responses to aerobic and resistance exercise in men addicted to methamphetamine during rehabilitation. Methods. Subjects were 10 men addicted to methamphetamine with an average age of 31.2 ± 6.2 years old, height: 173 ± 5.6 cm, weight: 73.66 ± 12.5 kg. In the first session the subjects were acquainted with the environment. The variables measured at the second session were physical and physiological characteristics. In the third and fourth sessions, projects to ensure the effectiveness of the pilot were conducted. In the fifth and sixth sessions which were spaced 7 days apart, aerobic and resistance exercises were carried out. The variables which were measured before and after exercise programs included heart rate, blood pressure and circulatory levels of serotonin and dopamine. Results. The increase in blood serotonin and dopamine levels after both aerobic and resistance exercise were significant (p < .05), but neither of the two aerobic and resistance exercise were superior to each other. In addition, decrease in systolic and diastolic blood pressure, heart rate, mean arterial pressure, pulse pressure and myocardial oxygen cost at some time intervals after these two exercises were significant ( p < .05), However, there were no significant changes in comparison of exercises (p > .05). Conclusions. Both of these exercises can be used as valuable support factors in treatment of addiction. Keywords: physical activity, methamphetamine, neurotransmitter, blood pressure.